L-Ornithine L-Aspartate for the Treatment of Sarcopenia in Chronic Liver Disease: The Taming of a Vicious Cycle - Roger F. Butterworth (Canadian Journal of Gastroenterology and Hepatology)
Sarcopenia is a common complication of cirrhosis with a negative impact on posttransplant outcome, health-related quality of life (HRQOL), and patient survival. Studies in experimental animals and in patients demonstrate that ammonia is directly implicated in the pathogenesis of sarcopenia in cirrhosis via mechanisms involving increased expression of myostatin and of autophagy markers such as LC3 lipidation and p62 leading to muscle dysmetabolism and sarcopenia. Paradoxically, skeletal muscle replaces liver as the primary ammonia-detoxifying site as a result of the modification of genes coding for key proteins implicated in ammonia-lowering pathways in cirrhosis. Thus, a vicious cycle occurs whereby hyperammonemia causes severe muscle damage and sarcopenia that, in turn, limits the capacity of muscle to remove excess blood-borne ammonia and the cycle continues. Randomized clinical trials and meta-analyses confirm that L-ornithine L-aspartate (LOLA) is an effective ammonia-lowering agent currently employed for the treatment of hepatic encephalopathy (HE) that stimulates both urea synthesis by residual hepatocytes and muscle glutamine synthesis together with putative hepatoprotective actions. Treatment of cirrhotic patients with LOLA limits ammonia-induced sarcopenia by improving muscle protein synthesis and function. It is conceivable that the antisarcopenic action of LOLA contributes to its efficacy for the treatment of HE in cirrhosis.